Something Else Going On? Diagnostic Uncertainty in Children with Chronic Pain and Their Parents - Vivek Tanna; Lauren C. Heathcote; Marissa S. Heirich; Gillian Rush; Alexandra Neville; Melanie Noel; Joshua W. Pate; Laura E. Simons (MDPI AG, 2020)
Diagnostic uncertainty, the perceived lack of an accurate explanation of the patient's health problem, remains relatively unstudied in children. This study examined the prevalence, familial concordance, and correlates of diagnostic uncertainty in children and their parents presenting to a multidisciplinary pain clinic in the United States. One hundred and twenty-six parents and 91 of their children (Mage = 13.93 years, range = 8-18 years) completed a brief three-item measure of diagnostic uncertainty, as well as measures of pain-related distress and functioning. Forty-eight percent of children and 37% of parents believed something else was going on with the child's pain that doctors had not found out about yet. Across the three items, 66%-77% of children and their parents agreed in their endorsement of diagnostic uncertainty. Parents who believed that something else was going on with their child's pain had children with higher avoidance of pain-related activities (F = 5.601, p = 0.020) and lower pain willingness (F = 4.782, p = 0.032). Neither parent nor child diagnostic uncertainty was significantly related to the child's pain-related functioning. Diagnostic uncertainty, particularly in parents, is relevant in the experience of pediatric chronic pain and warrants further investigation as both a risk factor and therapeutic target.